Diversidade de Formicidae (Hymenoptera) em um fragmento de Floresta Estacional Semidecídua no Noroeste do Estado de São Paulo, Brasil. - Castilho, Gracieli Araújo [UNESP]; Noll, Fernando Barbosa [UNESP]; Silva, Eliani Rodrigues da; Santos, Eduardo Fernando dos (My University, 2011)
(Ant diversity (Hymenoptera) in a fragment of Semidecidual Seasonal Forest in Northwest of São Paulo State, Brazil). Due to scarce knowledge about ant fauna from Northwestern São Paulo State, the present study aimed to know the taxonomic diversity of Formicidae, relating the results to climatic variation along of one year. The samples were gotten monthly, using pitfall traps. It was sampled 25 species of 15 genera and seven subfamilies. Myrmicinae was the sampled richest subfamily, follows by Formicinae and Ponerinae. According Wilcoxon test, the species richness, equability and diversity estimated by Simpson index were significantly higher in the rain season. The obtained results suggest that the abundance of ants is significantly related to the temperature variation, while the ant assemblage structure is related to thermal and pluviometric variations.

(Diversidade de Formicidae (Hymenoptera) em um fragmento de Floresta Estacional Semidecídua no Noroeste do estado de São Paulo, Brasil). Devido ao escasso conhecimento sobre a mirmecofauna do Noroeste do estado de São Paulo, o presente estudo teve como objetivo conhecer a diversidade de Formicidae, relacionando os resultados com a variação climática ao longo de um ano. As coletas foram feitas mensalmente, utilizando armadilhas do tipo pitfall. Foram amostradas 25 espécies de 15 gêneros e sete subfamílias. Myrmicinae foi a subfamília com o maior número de espécies amostradas, seguida por Formicinae e Ponerinae. De acordo com o teste de Wilcoxon, a riqueza, a equabilidade e a diversidade de espécies, foram significativamente maiores na estação chuvosa. Os resultados obtidos sugerem que a abundância de formigas está significativamente relacionada à variação da temperatura, enquanto que a estrutura da comunidade está relacionada às variações térmicas e pluviométricas.
Keywords: Pitfall; Mata Atlântica; mirmecofauna; sazonalidade; Pitfall; Atlantic Forest; mirmecofauna; seasonality